KALIMAT IMPERATIF DALAM NOVEL SELENA KARYA TERE LIYE (KAJIAN SINTAKSIS) - Sri Wulandari (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
Novel as a form of literary work is expected to produce positive values ​​for readers, so that they can be sensitive to problems related to social life and encourage good behavior. Novels usually tell about the realities of human life with the environment around them. This research focuses on the form and meaning of imperative sentences in Tere Liye's novel Selena. The purpose of this study was to determine the form and meaning of imperative sentences in Tere Liye's Selena novel. This study uses descriptive qualitative data analysis techniques. Data collection was done by observing method through note taking technique. The research results show that there are conclusions in the novel Selena by Tere Liye, namely finding the form of the imperative Intrasitive sentence and found 8 meanings, namely the imperative request sentence, and the imperative request sentence, the imperative expectation sentence, the imperative sentence for prohibition, and the imperative sentence for allowing, the imperative sentence for invitation, From the data and findings, there are 80 imperative sentences. The most common found were imperative sentences of request with as much as 48 data, while the least was the imperative sentences of leaving with 2 data.